Trophic interactions between a native Catfish (Trichomycteridae) and a non-native species, the Rainbow Trout, in an Andean stream, San Juan, Argentina. Issue 4 (2nd October 2017) - Garcia, M. I.; Acosta, J. C.; García, M. L.
Abstract : The trophic relationship between Torrent Catfish ( Hatcheria macraei) and Rainbow Trout ( Oncorhynchus mykiss ) was studied in a lotic Andean system of Argentina to examine whether these fish compete for the same food resources. Fishes were sampled seasonally, in autumn, spring, and summer. Hatcheria macraei and O. mykiss presented a carnivorous generalist feeding strategy. Trout diet was dominated by aquatic macroinvertebrates, and terrestrial invertebrates were an important component in summer. Large-sized Rainbow Trout fed on Catfish, which in turn preyed mainly on Chironomidae and Elmidae larvae. During flood periods, the Trout diet, as well as that of the Catfish, was mainly composed of clingers (Elmidae and Chironomidae) and particularly in the case of Catfish, burrowers (Oligochaeta) were found. We found an elevated dietary overlap between Trout and Catfish with seasonal changes. Our results suggest that coexistence of Trout and Catfish depends on input of terrestrial invertebrates, and the feeding of Catfish on small prey.